Advances in the diagnosis, treatment and control of HIV associated tuberculosis - Kirenga, Bruce James; Chanda, Duncan M; Muwonge, Catherine M; Yimer, Getnet; Adatu, Francis E; Onyebujoh, Philip C (African Journal of Infectious Diseases (AJID), 2012)
There has been an increase in the number of published tuberculosis/HIV (TB/HIV) research findings in recent times. The potential impact of these findings on routine care has informed this review which aims at discussing current concepts and practices underpinning TB/HIV care and control. Diagnosis: Any HIV infected person with a cough of any duration is currently considered a TB suspect. Preliminary results also show that the diagnostic yield of same day sputum samples (front loading) is comparable to two day samples. Laboratory diagnosis is shifting from Ziehl–Neelsen (ZN) smear microscopy and solid culture to fluorescent microscopy, molecular tests and liquid culture. Treatment: Concomitant TB/HIV therapy improves survival and WHO has recommended ART for all TB/HIV patients. Unless CD4 cell counts are less 50 cells/µl, ART can be deferred until end of intensive phase. Evidence of survival benefit at high CD4 cell counts is still lacking. New TB drugs and treatment shortening studies are underway but so far no new TB drugs has been added to the current arsenal and treatment duration still remains six months or more. TB control: WHO has recommended the 3Is (intensified TB case finding, isoniazid prophylaxis and infection control) for TB/HIV control in addition to effective therapy, Antiretroviral therapy and TB vaccines. Conclusion: There has been immense progress in TB/HIV research, however optimal management of HIV-Infected TB patients, will require further research and appropriate translation of emerging evidence to policy and practice.